Commodity and Institution Integration; A Model of Rural Economic Empowerment - ., Saifuddin; ., Suadi; ., Fadli (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTIn post-conflict, Aceh government has implemented various activities to empowerment people’s economy in rural areas. Especially for ex-combatants of Free Aceh Movement and conflict-victims communities in East Aceh district, Aceh government has carried out some activities to empower their economic. It includes the provision of palm oil, cattle and goats assistance. This study aims to develop a model of community economic empowerment through the integration of commodities and institutions. This research used qualitative approach, which data were analyzed in three steeps; data reduction, data display and conclusion. The results showed that the model of cattle-oil palm integration has not supported by integration of government and private institutions, so that empowerment program has not effect to raise their economic optimally.Keywords: Integration, Empowerment, Cattle, Palm Oil and InstitutionABSTRAKPasca konflik, Pemerintah Aceh telah melaksanakan berbagai kegiatan untuk pemberdayaan ekonomi masyarakat diwilayah pedesaan. Khusunya untuk mantan Kombatan Gerakan Aceh Merdeka dan masyarakat korban konflik di Kabupaten Aceh Timur, kegiatan pemberdayaan ekonomi yang dilakukan adalah memberikan bantuan kelapa sawit, sapi dan kambing kepada mereka dengan melibatkan berbagai lembaga termasuk lembaga swasta. Penelitian ini bertujuan untuk mengembangkan model pemberdayaan ekonomi masyarakat melalui integrasi antar komoditi dan sekaligus institusi. Penelitian ini menggunakan pendekatan kualitatif. Data dianalisis dalam tiga tahapan yaitu reduksi dan penyajian data serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa model integrasi sawit-sapi yang dilaksanakan oleh masyarakat tidak di dukung oleh integrasi antar institusi. Akibatnya program pemberdayaan tidak memberi dampak terhadap peningkatan percepatan ekonomi masyarakat secara optimal.Kata Kunci: Pemberdayaan, Integrasi, Sapi, Sawit dan Lembaga